Relationship between blood pressure and stroke risk in patients with symptomatic carotid occlusive disease. - Rothwell, P; Howard, S; Spence, J (2003)
BACKGROUND AND PURPOSE: Blood pressure lowering in patients with a previous transient ischemic attack (TIA) or stroke reduces the risk of recurrent stroke and coronary vascular events. However, there is uncertainty about the risks and benefits in patients with severe carotid occlusive disease, particularly those with a carotid occlusion or bilateral > or =70% carotid stenosis in whom cerebral perfusion is often impaired and may depend directly on systemic blood pressure. Therefore, we studied the effect of carotid artery disease on the relationship between blood pressure and stroke risk in patients with recent TIA or stroke. METHODS: We compared the relationship between blood pressure (systolic and diastolic blood pressures, pulse pressure) and stroke risk in TIA and stroke patients with documented stenosis of at least 1 carotid artery [European Carotid Surgery Trial (ECST) and North American Symptomatic Carotid Endarterectomy Trial (NASCET)] with that in TIA and stroke patients with a low prevalence of carotid disease [United Kingdom Transient Ischaemic Attack (UK-TIA) Aspirin Trial]. In ECST and NASCET, we also determined the relationship between blood pressure and stroke risk in patients with unilateral carotid occlusion and patients with bilateral > or =70% carotid stenosis. RESULTS: Stroke risk on medical treatment increased with blood pressure in ECST and NASCET, but the relationships were less steep than in the UK-TIA trial. The relationship between blood pressure and stroke risk was not affected by the presence of a unilateral carotid occlusion but was significantly affected by the presence of bilateral carotid stenosis > or =70% (interaction: systolic blood pressure, P=0.002; diastolic blood pressure, P=0.03; pulse pressure, P=0.003). In this group, the relationship was inverted because of the high stroke risks at lower blood pressures. This interaction was not present after carotid endarterectomy and was not present for the risk of myocardial infarction. CONCLUSIONS: The risk of stroke increases with blood pressure in the great majority of patients with symptomatic carotid artery disease, but the relationship is less steep than in other patients with TIA or stroke. The relationship is unaffected by unilateral carotid occlusion alone but is inverted in patients with bilateral > or =70% carotid stenosis, suggesting that aggressive blood pressure lowering may not be advisable in this group. These patients represent only a few percent of all patients with TIA or stroke but have a high risk of recurrent stroke.